Analysis of Collaborative Governance Policies in the Development of Marine Tourism in Indonesia - Suhardono, Edi; Rianto, Budi; ., Sulistiyanto; Amin, Moeh Faizal (Journal of Ecohumanism, 2024)
The purpose of this research is to examine how the performance of collaborative policies management of tourist destinations in Kebumen Regency Indonesia in the development of marine tourism to improve the economic sector. The qualitative method used in this research uses a marine ecotourism case study approach in Kebumen Regency, based on the post-positivist philosophy to study the state of major natural tourism objects with inductive data analysis. The focus of this research includes: (1) Initial conditions; (2) Process Components; (3) Structure and Governance; (4) Contingencies and Constraints; (5) Results and Accountability. The results showed that the policy performance of collaborative patterns of marine tourism development in Kebumen Regency has generated new ideas and can still be improved in the aspects of process components, contingencies and constraints as well as output and accountability. good in some based on the natural conditions of local tourist destinations.